Investigating the impact of lipid oxidation on the duck odorous smell during storage and reheating based on lipidomics - Gaiming Zhao; Ying Zhang; Jiali Zhang; Sen Wang; Ke Wang; Long Xu; Qiuhui Zhang; Chaozhi Zhu (Current Research in Food Science)
In the actual production of duck meat, the cooking time for marinated and sliced duck products is around 30 min. Before consumption, it is recommended to use a water bath for reheating at 75 °C for 10 min. However, many consumers reflect that after reheating, there will be an unpleasant smell, affecting the quality of food. Therefore, to investigate the effects of lipid oxidation on the duck odorous smell during heat treatment and reheating, lipid oxidation, sensory evaluation and lipidomics were performed on raw duck meat, 90 °C processed, and reheated cooked duck meat stored at 4 ± 1 °C for 3 and 7 days, respectively. The results showed that the duck odorous smell increased after heat treatment and reheating. A total of 26 lipid subclasses and 519 lipid molecules were identified in duck meat based on lipidomics. Phosphatidylcholine (PC) and phosphatidylethanolamine (PE) in duck meat phospholipids played an important role in the production of duck odorous smell. These findings may contribute in reducing duck odorous smell by targeted inhibition of lipid oxidation.